The Antecedents of the Success of the elderly care home business in Bangkok and the surrounding areas - Fongtanakit, Rachada (Journal of Posthumanism, 2024)
The results of the research found that 1) the level of support from the government sector's Executive Leadership Management Service innovation at the highest level and the success of the elderly care home business are at a high level. 2) Influence of government support, executive leadership, management, and service innovation that affect the success of the elderly care home business There are calculated statistical values. Chi-square value = 70.00, df = 57, p-value = 0.116, GFI = 0.97, AGFI = 0.94, RMR = 0.016, RMSEA = 0.028, CFI = 1.00, and CN = 355.21. The results of the study will be used as a guideline. To further develop the business of elderly care facilities in Bangkok and surrounding areas.